Analisis Pengakuan Pendapatan dan Biaya Atas Laporan Keuangan Secara Fiskal Pada CV Setia Kawan Abadi - Damayanti, Selfia; Hidayat, R. Taufik; Sugiyanta, Yohanes (Mulia Pratama, 2024)
This study aims to find out how revenue recognition in the fiscal financial statements of CV Setia Kawan Abadi, knowing how to recognize costs in CV Setia Kawan Abadi fiscal financial reports. And find out what income and expenses are in CV Setia Kawan Abadi financial reports. Which is appropriate and not in accordance with the tax law. The type of data used in this study is quantitative data. The data source used is secondary data. The data source used in this study was taken from financial reports obtained directly from the company. In this study, the sample used by the author is the fiscal profit and loss statements for 2019 and 2020 at CV Eternal Faithful Friend. The data collection method used by the author is library research and field research. And the method of data analysis used by the author is quantitative analysis and descriptive analysis. The results of the research conclude that (1) Recognition of income for 2019 and 2020 in the financial statements of CV Setia Kawan Abadi is still based on the Financial Accounting Standards for Micro, Small and Medium Entities and has not based itself on the Tax Law Number 36 of 2008. (2) Recognition of 2019 and 2020 expenses in the financial statements CV Setia Kawan Abadi has not followed the definition of costs according to the Tax Law Number 36 of 2008. (3) Revenues and expenses that are not yet in accordance with the tax law include, among others, current account income of Rp. 3,875,437 in 2019, in 2020 it is Rp. 1,265,893, telephone costs Rp. 18,847,101 in 2019, Rp. 8,993,213 in 2020, PP 28/2018 tax (final) Rp. 18,970,480 in 2019, in 2020 the PP 23/2018 tax (final) is Rp. 13,490,191, current account service tax is Rp. 775,087 in 2019, in 2020 Rp. 253,179.